MENINGKATKAN AKTIVITAS BELAJAR DAN DISIPLIN SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Sarwono, Sarwono (Jurnal Phederal Penjas, 2014)
Passive and undisciplined behavior of students on the learning process implemented physical education is a frequent problem encountered by the teachers, especially for young teachers. In fact, an experienced teacher also still encounter students who are undisciplined and passive behavior of students in learning. Various efforts and strategies to improve student learning activities and disciplines need to be owned by the teachers as to increase its efforts to avoid these problems become more severe. Some of the guidance system of discipline is more emphasis on extrinsic motivation, while others emphasize the intrinsic motivation. Regardless of the coaching system selected by the teacher disciplined by the teacher, the application development needs to be done consistently disciplined, rigorous, and still appreciate the feelings and self-esteem.